A founder truncating variant in GDF1 causes autosomal‐recessive right isomerism and associated congenital heart defects in multiplex Arab kindreds. Issue 5 (7th March 2020) - Marek‐Yagel, Dina; Bolkier, Yoav; Barel, Ortal; Vardi, Amir; Mishali, David; Katz, Uriel; Salem, Yishay; Abudi, Shachar; Nayshool, Omri; Kol, Nitzan; Raas‐Rothschild, Annick; Rechavi, Gideon; et al.
Abstract: The genetic basis of congenital heart malformations associated with disruption of left–right (L–R) asymmetry is broad and heterogenous, with variants in over 25 genes implicated thus far. Of these, deleterious variants in the Growth/Differentiation Factor 1 ( GDF1 ) gene have been shown to cause heterotaxy with varied complex heart malformations of left–right patterning, in 23 individuals reported to date, either in monoallelic or biallelic state. We report three unrelated individuals exhibiting right isomerism with congenital heart defects, each originating from a consanguineous kindred of Arab‐Muslim descent. Using whole exome sequencing, a shared novel homozygous truncating c.608G > A (p.W203*) variant in the GDF1 gene was revealed as the molecular basis of their disease. Subsequently, targeted sequencing of this variant showed full segregation with the disease in these families, with a total of over 15 reportedly affected individuals, enabling genetic counseling, prenatal diagnosis, and planning of future pregnancies. Our findings further confirm the association of biallelic GDF1 variants, heterotaxy and congenital heart defects of left–right patterning, and expand the previously described phenotypic spectrum and mutational profile. Moreover, we suggest targeted screening for the p.W203* variant in relevant clinical circumstances.